2015
DOI: 10.1016/j.cis.2015.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the Young–Laplace equation and prediction of bubble interface in the presence of nanoparticles

Abstract: Abstract:Bubbles are fundamental to our daily life and have wide applications such as in the chemical and petrochemical industry, pharmaceutical engineering, mineral processing and colloids engineering. This paper reviews the existing theoretical and experimental bubble studies, with a special focus on the dynamics of triple line and the influence of nanoparticles on the bubble growth and departure process. Nanoparticles are found to influence significantly the effective interfacial properties and the dynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 122 publications
0
20
0
Order By: Relevance
“…It is related to the resolution of the measurement system. In order to clarify the relationship between the apparent contact angle and gravity, neglecting completely the disjoining pressure, we used the mechanical method of deriving the Young-Laplace equation [56], with consideration of the presence of hydrostatic pressure, liquid-vapor, solid-vapor, and solid-liquid interfacial tensions. And for this large drop, we consider a small rectangular section (ABCD, Figure 6) of the liquid-vapor interface at the three-phase contact line, where CD is a segment of the apparent three-phase contact line.…”
Section: Relationship Between Apparent Contact Angle Andmentioning
confidence: 99%
“…It is related to the resolution of the measurement system. In order to clarify the relationship between the apparent contact angle and gravity, neglecting completely the disjoining pressure, we used the mechanical method of deriving the Young-Laplace equation [56], with consideration of the presence of hydrostatic pressure, liquid-vapor, solid-vapor, and solid-liquid interfacial tensions. And for this large drop, we consider a small rectangular section (ABCD, Figure 6) of the liquid-vapor interface at the three-phase contact line, where CD is a segment of the apparent three-phase contact line.…”
Section: Relationship Between Apparent Contact Angle Andmentioning
confidence: 99%
“…The basic modeling idea is based on the so-called Young-Laplace equation, see [28]. We assumed to have quasi-static cases, while we had static pressure, and the surface tension forces were also effective elements, see [29].…”
Section: Near-field Modelmentioning
confidence: 99%
“…The Young-Laplace-equation is derived by the balance of the liquid-gas interface, see [29], where we have:…”
Section: Near-field Modelmentioning
confidence: 99%
“…Snabre and Magnifotcham [ 13 ] considered the continuous emission of gas bubbles from a single ejection orifice immersed in water–glycerol systems and analyzed the effects of fluid viscosity, gas flow rate, orifice diameter, and liquid depth on the bubble stream dynamic to derive an expression for the net viscous force acting on the surrounding fluid. Vafaei and Wen [ 14 , 15 ] injected air into deionized water and nanofluids to observe the effect of nanoparticles on the three-phase contact line and bubble morphology, and used the Young–Laplace equation to predict the evolution of bubbles. It was found that within a few milliseconds before the bubble detaches, the Young–Laplace equation could no longer accurately describe the real-time boundary of the bubble.…”
Section: Introductionmentioning
confidence: 99%